Mechanisms explaining the birthplace effect for male elite football players. Issue 5 (4th March 2021) - van Nieuwstadt, Michiel H. H.; Das, Marjolijn; Elferink-Gemser, Marije T.
ABSTRACT: Earlier research shows that wide regional variations exist in the success of athletes' talent development but is divided with respect to the role of urbanity: both low and high urbanity have been identified as settings that contribute to the presence of talent hotspots. In this article, we intend to provide more insight into the role of urbanity in talent development in Dutch football. We used public data on the regional background of male elite players (N = 825) and combined this with public data on municipal characteristics from Statistics Netherlands and other sources: urbanity, football participation, instructional resources and population composition effects (migration background and income of inhabitants). Linear regression analysis showed that football participation, the proportion of non-western migrants and median income predict "talent yield", i.e., the proportion of young people that reach an elite level in a municipality. Urbanity does not have an independent influence when the proportion of non-western migrants in the municipality is taken into account. The presence of instructional resources does not have an independent influence. The results suggest that characteristics of the built environment, such as indoor and outdoor play opportunities, may be less influential in talent development than previously assumed.